Therapeutic management versus biological constituents of sub-oestrous crossbred cows of Asom - BONIA, K K; BAISHYA, N (The Indian Journal of Animal Sciences, 2011)
The present work was undertaken to observe efficacy of some drugs for therapeutic management of sub-oestrous crossbred cows. A total of 60 confirmed sub-oestrous cows were considered. Cows were divided into 6 groups each group comprising 10 cows. Respective cyclic group of cows were treated with prostaglandin 500 Î¼g on day 10, estradiolvalerate 30 mg on day 10 and at early oestrus, laboratory made mineral mixture (aauvetmin), aauvetmin plus multivitamins and a herbal drug stenot bolus. The mean time interval from last treatment to onset of induced oestrus was shortest (3.25Â±0.25 days) with highest conception on first insemination after treating with cloprostenol injection. Oral administration of balanced mineral mixture along with multivitamins was also found to be cost effective. Regular monitoring of vulvar swelling might be useful from breeding point of view. The serum calcium, inorganic phosphorus, sodium, potassium, magnesium, cobalt, total protein were not much altered whereas, glucose level was dropped to lower level on the day of onset of oestrus. The level of cholesterol and alkaline phosphatase was elevated whereas when zinc concentration was increased, the iron and copper decreased on the day oestrus in all responded cows. Moreover, when 17ÃŸ- estradiol in blood was reached highest concentration, progesterone concentration decreased to the lowest but not below 0.50 ng/ml, while cortisol was at higher level on the day of induced oestrus than at before treatment in all responded cows.